A review of early warning methods of thermal runaway of lithium ion batteries. (1st August 2023) - Kong, Depeng; Lv, Hongpeng; Ping, Ping; Wang, Gongquan
Abstract: Lithium-ion batteries (LIBs) are booming in the field of energy storage due to their advantages of high specific energy, long service life and so on. However, thermal runaway (TR) accidents caused by the unreasonable use or misuse of LIBs have seriously restricted the large-scale application of LIBs. Avoiding TR through advance warning has been becoming an increasing focus of research by scholars. In view of this, we provide a comprehensive review of TR warnings for LIBs. In this paper, an analysis of the existing monitoring parameters of the TR process is presented, and the sensitivity and robustness of multiple warning methods for the same characteristic parameters are compared. Subsequently, this is followed by a presentation of early warning applications in portable devices, electric vehicles and energy storage systems. Finally, combining the existing warning methods with the system's operational data, the future warning methods are envisioned. Highlights: To present a comprehensive review on early warning method of lithium ion battery thermal runaway To review the warning methods for relevant characteristics and obstacles To discuss the warning methods widely used in portable equipment, electric vehicles and energy storage power plants